Kualitas Pelayanan dalam Pembuatan Akta Kematian Melalui Sobat Dukcapil di Dinas Kependudukan dan Pencatatan Sipil Kota Tangerang - Tri Inka Indra Utama; Nida Handayani (Jurnal Media Administrasi, 2024)
In making death certificates, the Tangerang City Dukcapil Department provides services for making death certificates through Sobat Dukcapil to make it easier for the people of Tangerang City to process population documents, but with the existence of the Sobat Dukcapil application there are still problems regarding the system which is hampered, the lack of public understanding of using the Sobat Dukcapil application so that the service in making deeds death through dukcapil friends is still not effective. The purpose of this research is to determine and analyze the quality of service in making death certificates through Sobat Dukcapil at the Tangerang City Population and Civil Registration Service. The data collection techniques used are interview, observation and documentation techniques. Using Potter's theory (2003), namely the theory of service quality which has 6 indicators, the first is Appropriate and Relevant, the second indicator is Available and Affordable, the third indicator Can guarantee a sense of justice, the fourth indicator is Acceptable, the fifth indicator is Economical and Efficient, the sixth indicator is Effective. The results of the research from 6 indicators concluded that the indicators were appropriate and relevant because the presence of dukcapil friends could make it easier for people to submit requests for death certificates, only there were problems in the server error section. The available and affordable indicator concludes that it is still not affordable because there are still technical problems because the Android and iOS based ones are still temporarily deactivated and are still in the process of system maintenance. Indicators can guarantee a sense of justice that does not differentiate between certain groups, all are equally open and provide justice for society. Acceptable indicators conclude that the technical method is very easy to process on time, sometimes there are still some who don't understand how to use it. The economic and efficient indicators conclude that it is still not economical because registration of death certificates is still done offline. The effective indicator concludes that it is still not said to be effective because there are still problems with the system server still being maintained so that it becomes a technical obstacle.